Jurisdiction over International Crimes: The International Criminal Court and Other Ways of Ending Impunity - Valusha, Irina; Boom, Maryna van den (2023)
The book addresses the challenges and limitations in prosecution of individuals who committed crimes under international law. The individual criminal responsibility is broadly recognized and based on the understanding of the feasibility of such accountability in the present era. The Nuremberg Trials in 1946 marked a pivotal moment, establishing the first international tribunal for individuals and initiating a new chapter in international law’s pursuit of perpetrators threatening common values. The establishment of the permanent International Criminal Court (ICC) under the Rome Statute in 1998 and its operations since July 2002 show that its jurisdiction has not effectively curtailed the impunity of dictators, tyrants, and torture servants, especially in non-member States. Motivated by these shortcomings, the authors have analyzed the ICC’s procedural capacity to prosecute offenders from non member States to the Rome Statute and explored alternative jurisdiction modes over international crimes committed by individuals. The book advocates a broader application of the universal jurisdiction principle, recognizing the limitations of ad hoc criminal tribunals, hybrid courts, and the practical constraints of the ICC. The authors propose that, in addition to the ICC, international organizations and national states—especially those progressing toward the rule of law—can enhance the international justice system. Their suggestions include supporting civil society, establishing independent investigative mechanisms, maintaining human rights monitoring processes, and sharing best practices in investigating international crimes, including those covered by the Rome Statute, within national legal systems that apply the universal jurisdiction principle.